Oxford illustrated encyclopedia: Vol.2 - The nature world (New York, 1993)
The book describes the natural world for living organisms alone comprise over five million known species (for which over 90 per cent are animal), with possibly twice as many still unclassifield. It also has a number of entries on the more important fossils and extinct forms of animals and plants
Keywords: encyclopedias and dictionaries